Study on the Optimization of Implementation Time for the Construction of the Baraka Sports Facility Center (APBD PEN) Kab. Enrekang South Sulawesi - Fatmawaty Rachim; Mahyuddin; Fitriah; Erdawaty (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
In some projects, there are often delays in the completion of work, especially during construction work. To reduce the occurrence of cost overruns, it is necessary to optimize work time that is more carefully planned so that work delays can be avoided. In the field of construction engineering, the Microsoft Project application is used to manage plans or task times so that an ongoing project can be evaluated according to all stages of tasks in the project. The implementation of the Baraka Sports Facilities Center Development Project in June to July 2022 shows the time or duration of the planned implementation of the roof work for 37 calendar days and after analyzing the data using Microsoft Project, the optimization time is 32 calendar days. For 32 days, by increasing the number of workers, the following adjustments were made to improve efficiency: a. For SCH 20, 4” pipework, 3 welders and 3 additional workers were added; b. For batten work with CNP 150.50.20.2, 3 craftsmen and 3 additional workers were added; c. For bitumen asphalt roof covering work (CTI), 7 workers and 7 handymen were added; d. For bitumen asphalt work, 1 worker and 1 handyman were added.